Impact of Combining Long-Term Subsoiling and Organic Fertilizer on Soil Microbial Biomass Carbon and Nitrogen, Soil Enzyme Activity, and Water Use of Winter Wheat - Yang, Yonghui; Li, Minjie; Wu, Jicheng; Pan, Xiaoying; Gao, Cuimin; Tang, Darrell W. S. (Frontiers in Plant Science, 2022)
Reductions in soil productivity may occur due to long-term suboptimal tillage and fertilization practices. The application of appropriate tillage (subsoiling) and fertilization (organic fertilizer) methods is an important practice for improving soil structure, water conservation, and soil productivity. A field experiment in eastern Henan province has been conducted since 2011 to explore the effects of subsoiling and organic fertilizer on winter wheat (Triticum aestivum L.) farming. We studied the effects of conventional tillage (CT), subsoiling (S), organic fertilizer (OF), and organic fertilizer combined with subsoiling (S+OF) treatments on dry matter accumulation (DM), water consumption (ET), water use efficiency (WUE) at different growth stages, yield, and water production efficiency (WPE) of wheat over three consecutive years from 2016 to 2019. We also analyzed soil structure, soil organic carbon, soil microbial biomass carbon and nitrogen, and soil enzymes in 2019. The results indicate that compared with CT, the S, OF and S+OF treatments increased the proportion of >0.25mm aggregates, and S+OF especially led to increased soil organic carbon, soil microbial biomass carbon and nitrogen, soil enzyme activity (sucrase, cellulase, and urease) across the various growth stages of winter wheat in 2019. S+OF treatment was most effective in reducing ET, and improving DM and WUE during the entire growth period of wheat, and also increased the total dry matter accumulation (Total DM) and total water use efficiency (total WUE) by 18.6%-32.0% and 36.6%-42.7% respectively in these three years. Wheat yield and WPE under S+OF treatment increased by 11.6%- 28.6% and 26.8-43.6% respectively in these three years. Therefore, S+OF treatment was the best practice in the east of Henan province.